Bad liar : a novel [large type] - Hoag, Tami (Hoag, Tami. Broussard and Fourcade, 2024)
A murder victim dumped at the dead end of a lonely country road, face and hands obliterated by a shotgun blast, is not the way sheriff's detective Nick Fourcade wants to start his week. His only lead takes him to the family of a hometown hero suddenly gone missing. Marc Mercier left his home for a weekend hunting trip and hasn't been seen since. Meanwhile, sheriff's detective Annie Broussard begins her first day back on the job after suffering a brutal attack by taking on the case of B'Lynn Fontenot, a mother desperate to find her grown son, a recovering drug addict. Robbie Fontenot has been missing for eight days, but the local police have no interest in the case, telling B'Lynn that an adult has the right to disappear, and a missing addict is no big surprise.